Association between thyroid autoimmunity and ovarian reserve in women with hypothyroidism - Morales-Martínez, Felipe A. (Thyroid Res, 2021)
BACKGROUND: The ovarian function and therefore the ovarian reserve may be compromised by the pathogenesis of autoimmune diseases of which, Hashimoto’s thyroiditis (HT) is the most common in women of reproductive age. Furthermore, a prolonged reduction in thyroid hormone concentration results in a broad spectrum of reproductive alteration. Previous reports in the literature have been controversial regarding the impact of hypothyroidism and alterations in the ovarian reserve. Thus, this prospective and comparative study aimed to evaluate the association of hypothyroidism with low ovarian reserve. MATERIALS AND METHODS: A subset of 27 patients with primary autoimmune hypothyroidism were compared to healthy women. The ovarian reserve was assessed through the anti-Mullerian hormone (AMH) and the antral follicle count (AFC). RESULTS: Overall, the two groups did not display significant differences in length of their menstrual cycles neither in the AMH serum levels nor the AFC. CONCLUSIONS: No significant alteration was found in the ovarian reserve of women with HT.